(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Milk is a major part of the human diet, as it is a source of high nutritional value by macronutrients (proteins, fats and sugars) with good amounts of calcium, magnesium, selenium, riboflavin, zinc, vitamin B12 and pantothenic acid. Milk powder products are susceptible to microorganism contamination due to their high content of nutrients and prone to change physicochemical properties when they are exposed to poor storage conditions. This study aims to monitor some microbiological properties of some milk powders in the local market of lattakia governorate, and study the effect of storage conditions on milk powders. Five samples of unpackaged whole milk powder and two samples of packaged whole milk powder were studied. The results showed that Moisture percentage of packaged and unpackaged milk powders were 0.3 ± 3.8 and 3.4 ± 0.4 respectively, therefor conforms to the Syrian National Standards. The results also showed that total bacterial counts of packaged and unpackaged milk powders were 0.12×± 0.08 CFU/g and 3.45×± 0.38 CFU/g respectively, these products have been free of coliform and salmonella, therefor conforms to the Syrian National Standards.